Hydrological and Ecological Controls on Autochthonous Carbonate Deposition in Lake Systems: A Case Study From Lake Wuliangsu and the Global Perspective. Issue 12 (24th June 2019) - Sun, Dayang; He, Yuxin; Wu, Jinglu; Liu, Weiguo; Sun, Yongge
Abstract: Based on ~150‐year of sedimentary records, we identify that autochthonous carbonate deposition in Lake Wuliangsu, in the upper reaches of the Yellow River, was independent of both hydrological and ecological variations before 1965, influenced by hydrological changes due to agricultural activities during 1965–1990, and slightly impacted by higher productivity under the eutrophication process after 1990. By comparing with data from lakes across the globe, we find that lake size and lake stratification control the contribution of recycled organic carbon to autochthonous carbonate deposition. Continuous mixing and aeration in shallow lakes facilitate the transformation of organic carbon into 29–45% of sedimentary carbonate, different from large and deep lakes (2–25%). Organic carbon recycling in lakes remains generally stable or decreases under the pressure of lake eutrophication, requiring further investigations on whether more organic carbon will be buried in the carbonate form. Plain Language Summary: The mechanisms that control the deposition, on the bottom of lakes, of carbonate matter that forms within the lakes themselves, are important for the carbon cycles at regional and global scales. Here we present data of carbonate content and carbon isotope composition from the past ~150 years recorded at Lake Wuliangsu, where the historical hydrological and ecological conditions have been well studied. We first investigate the factors that control the deposition of carbonate matter and calculate how much of it derives from recycled organic carbon using a carbon isotope mass‐balance model. Furthermore, we compile published data from lake systems across the globe and we incorporate them into our framework, so as to seek a better understanding of organic carbon recycling in a global perspective. Finally, we find that the size of the lake (area and depth) and the lake stratification play a key role in determining the contribution of recycled organic carbon to the overall carbonate deposition. Key Points: Carbonate deposition in Lake Wuliangsu is influenced by human‐induced hydrological and ecological changes after 1965 In Lake Wuliangsu, recycling of organic carbon contributes more than 30% of the sedimentary carbonate In the global perspective, lake size and lake stratification are crucial for contribution of recycled organic carbon to carbonate